Pengaruh Partisipasi Angkatan Kerja (PAK) Dan Tingkat Pengangguran Terbuka (TPT) Terhadap PDRB Di Provinsi Sumatera Utara - Andini; Samsuddin, M. Afdal (Jurnal Ilmu Ekonomi dan Bisnis, 2025)
This study aims to analyze the extent to which labor force participation and open unemployment rates influence the Gross Regional Domestic Product (GRDP) across 33 regencies/cities in North Sumatra Province over the period 2019–2023. Utilizing panel data regression with a Fixed Effect Model, the results show an R-squared value of 99.12%. Labor force participation has a positive coefficient (44.61) but is statistically insignificant (p = 0.11), while the open unemployment rate has a negative coefficient (−237.44) and is significant at the 90% confidence level (p = 0.096). These findings suggest that increasing the quantity of labor force participation alone is insufficient to boost GRDP without improving labor quality, whereas reducing unemployment has been shown to effectively enhance regional economic output.